Assessing serum cytokine and immunoglobulin levels in patients with allergic rhinitis and allergic rhinoconjunctivitis before and after treatment supplemented with macromycetes - V. K. Bogdanov; S.M. Pukhlyk; M.B. Makarova; S.I. Poliakova; K.G. Bogdanov (Ukrainian Society of Ophthalmologists, 2023)
Background: In recent decades, the prevalence of allergic rhinitis (AR) has been increasing all over the world including Ukraine. Allergic rhinoconjunctivitis (ARC) is one of the most common clinical forms of AR. An imbalance between pro-inflammatory and anti-inflammatory cytokines is known to have a key role in allergic inflammation. Purpose: To compare cytokine and immunoglobulin levels among patients with AR and ARC treated with different therapeutic options. Material and Methods: Forty patients with AR and ARC (age range, 20 to 46 years) were included in the study. Disease duration ranged from 6 months to 2 years. Patients were divided into two subgroups of 20 patients each. Patients of subgroup 1 received the basic therapy (a 10-mg loratadin tablet daily and mometasone furoate nasal spray at a dosage of 200 μg once daily), whereas patients of subgroup 2, the basic therapy plus polypore macromycetes (Astmagan), one capsule twice daily. Treatment course duration was 90 days. The control group was composed of 25 healthy individuals. A comprehensive clinical immunological examination was conducted at baseline and on the completion of the treatment course. Enzyme-linked immunosorbent assay kits were used to determine serum levels of immunoglobulins A (IgA), IgM, IgG, and IgE, and cytokines (gamma interferon (IFN-γ) and IL4). Results: At baseline, serum levels of IgA, IgM and IgE were almost twice as high (р = 0.0008; 0.0005; and 0.0001, respectively); IgG, 1.2 times higher (р = 0.001); pro-inflammatory cytokine IL4, 3.5 times higher (р = 0.0001); and anti-inflammatory cytokine IFN-γ, 2.4 times lower (р = 0.0001) in patients with AR and ARC compared to controls, and these differences were significant. Astmagan, when used as an adjunct to the basic treatment of AR and ARC, contributed to 8%, 17%, 16.2%, 7.3% and 6.0% greater decreases in the serum levels of IgA, IgM, IgE, IgG and IL4, respectively, and a 16.6% greater increase in the serum level of IFN-γ compared to the basic treatment only, and these differences were significant, with an improvement in immune response to therapy.